Politeness Strategies Used in English Talk Shows: A Pragmatic Perspective - Ekanaafi, Dhyta; Afifah, Wiwiek (SENTRI: Jurnal Riset Ilmiah, 2026)
This study explores the use of politeness strategies in English talk shows from a pragmatic perspective, focusing on how hosts and guests manage face-threatening acts (FTAs) in public, semi-formal communication settings. Drawing on Brown and Levinson’s (1987) politeness theory, the study analyzed 276 utterances from three selected episodes of three popular talk shows: The Ellen DeGeneres Show (featuring Michelle Obama), The Tonight Show Starring Jimmy Fallon (featuring Selena Gomez), and The Graham Norton Show (featuring Adele). Each utterance was categorized according to four politeness strategies: bald on-record, positive politeness, negative politeness, and off-record. The findings reveal that positive politeness emerged as the most frequently used strategy (51.4%), reflecting the need to establish friendliness, reduce social distance, and maintain audience engagement in entertainment-oriented public discourse. Negative politeness accounted for 24.6%, followed by off-record strategies (13%) and bald on-record strategies (10.9%). These results suggest that politeness in media discourse serves not only interpersonal functions but also supports genre conventions and audience expectations. This study contributes to pragmatics and media discourse by providing empirical insights into how linguistic strategies are adapted to manage face, engage audiences, and construct public persona in talk show interactions.